Deciphering colorectal cancer genetics through multi-omic analysis of 100,204 cases and 154,587 controls of European and east Asian ancestries - Fernandez-Rozadilla, Ceres; Timofeeva, Maria; Chen, Zhishan; Law, Philip; Thomas, Minta; Schmit, Stephanie; Díez-Obrero, Virginia; Hsu, Li; Fernandez-Tajes, Juan; Palles, Claire; Sherwood, Kitty; Briggs, Sarah; et al. (Nature genetics, 2022)
Colorectal cancer (CRC) is a leading cause of mortality worldwide. We conducted a genome-wide association study meta-analysis of 100,204 CRC cases and 154,587 controls of European and east Asian ancestry, identifying 205 independent risk associations, of which 50 were unreported. We performed integrative genomic, transcriptomic and methylomic analyses across large bowel mucosa and other tissues. Transcriptome- and methylome-wide association studies revealed an additional 53 risk associations. We identified 155 high-confidence effector genes functionally linked to CRC risk, many of which had no previously established role in CRC. These have multiple different functions and specifically indicate that variation in normal colorectal homeostasis, proliferation, cell adhesion, migration, immunity and microbial interactions determines CRC risk. Crosstissue analyses indicated that over a third of effector genes most probably act outside the colonic mucosa. Our findings provide insights into colorectal oncogenesis and highlight potential targets across tissues for new CRC treatment and chemoprevention strategies.
Veröffentlicht: 20. Dezember 2022
Gesehen am 13.12.2023